The Myth of Openness and Secrecy in Intimate Relationships: The Case of Spouses of Mixed-Orientation Marriage. Issue 6 (12th May 2017) - Adler, Adir; Ben-Ari, Adital
ABSTRACT: The phenomenon of mixed-orientation marriages, in which one of the partners is straight and the other is non-straight, is invisible, yet not insignificant. Focusing on gay and bisexual men who are married to straight women, this article was designed to explore one of the essential themes in their relationship: the dynamics between secrecy and openness regarding the men's sexual orientation and gay practices. Based on the phenomenological paradigm, 38 men and eight women of mixed-orientation marriages in Israel were interviewed and shared their subjective life reality. Six patterns of secrecy and openness were identified, including complete secrecy, conspiracy of silence, initiated concealment (of the husband and wife), disloyalty/violation of the agreement, selective sharing, and complete openness. The findings challenge the idea that secrecy is detrimental and openness is beneficial in the context of mixed-orientation marriages. Findings are discussed within the framework of the dialectical approach.